Risk factors of post-stroke depression after acute ischemic stroke - A prospective study from a tertiary care hospital in South India - Roy Thomas (Asian Journal of Medical Sciences, 2023)
Background: Post-stroke depression is a major cause for poor functional and rehabilitation recovery. Aims and Objectives: The aims of the study were to determine risk factors causing depression in acute ischemic stroke. Materials and Methods: Prospective cohort study was conducted in acute ischemic stroke patients between January 2023 and April 2023 at Travancore Medical College, Kerala. They were divided into – ischemic stroke patients with depression and without depression. Variables studied – age, gender, marital, educational, occupation, socioeconomic status, national institute of health stroke scale (NIHSS) at admission, modified Rankin Scale (mRS) at 1 month, stroke lateralization, risk factors, and lobe and site. Results: Among 270 patients, 164 (60.7%) were male, 254 (94.1%) were above 50 years, 250 (92.6%) had marriage partner, 164 (60.7%) unemployed, 138 (51.1%) belonged to middle socioeconomic status, and 172 (63.7%) from rural areas. About 91 (33.7%) were in ischemic stroke patients with depression group. In univariate analysis, marriage, socioeconomic status, subcortical location, left hemisphere, severe NIHSS, and high mRS were associated with post-stroke depression. In multivariate analysis, socioeconomic status, subcortical location, and left hemisphere were significant risk factors. Strongest predictor was subcortical location. Conclusion: Early identification of following risk factors – socioeconomic and marital status, subcortical location, left hemisphere lesion, severe NIHSS, and high mRS in acute stroke patients may help to identify those who are vulnerable for post-stroke depression.